The Impact of an EFL Graduate Tutoring Experience at a University Context (2024)
ABSTRACT: Professional development strategies are essential for English as a Foreign Language (EFL) graduate tutors to better perform their language instruction with their students. This chapter describes a professional development initiative and a teaching practice on the topic of tutoring done by a group of EFL graduate tutors at a public university in Medellín - Colombia. Following a visionary professional development strategy (Díaz-Maggioli, 2004), a case study was used as a research guide, and three instruments were applied during different practices of tutoring sessions in English as a foreign language to gather information. Aiming to get the student’s rapport, diaries of EFL graduate tutors, interviews, and tutees’ materials were implemented. Findings suggest that graduates’ learning is enhanced if they belong to a study group whose theory and practices are focused on improving their teaching experiences. Regarding the students, it may be concluded that they showed a good attitude and increased their autonomy level toward their learning process after the tutoring sessions while building some rapport. This process also helped students acquire new vocabulary knowledge and provided them with more pedagogical strategies to develop linguistic activities. Conclusions emphasize the importance of designing a tutoring session protocol that includes an introduction, instruction, and assessment. Finally, recommendations involve a list of do’s and don’ts when conducting a tutoring session.